53+103y=3y-2

Combine 103 and y.

53+10y3=3y-2

Subtract 3y from both sides of the equation.

53+10y3-3y=-2

To write -3y as a fraction with a common denominator, multiply by 33.

53+10y3-3y⋅33=-2

Combine -3y and 33.

53+10y3+-3y⋅33=-2

Combine the numerators over the common denominator.

53+10y-3y⋅33=-2

Combine the numerators over the common denominator.

5+10y-3y⋅33=-2

Simplify the numerator.

Multiply 3 by -3.

5+10y-9y3=-2

Subtract 9y from 10y.

5+y3=-2

5+y3=-2

5+y3=-2

Multiply both sides of the equation by 3.

3⋅5+y3=3⋅-2

Cancel the common factor of 3.

Cancel the common factor.

3⋅5+y3=3⋅-2

Rewrite the expression.

5+y=3⋅-2

5+y=3⋅-2

Multiply 3 by -2.

5+y=-6

5+y=-6

Subtract 5 from both sides of the equation.

y=-6-5

Subtract 5 from -6.

y=-11

y=-11

Solve for y 5/3+10/3y=3y-2